2020
DOI: 10.1007/s12553-020-00459-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the tissue interaction between thermal ablation and cryotherapy as treatment for cervical precancerous lesions in an ex-vivo model

Abstract: Both cryotherapy and thermal ablation are treatment methods for cervical precancerous lesions in screening programs in resource constrained settings. However, for thermal ablation the World Health Organization stated that there is insufficient data to define a standard treatment protocol. This study used an ex-vivo model to compare the tissue interaction of both cryotherapy and thermal ablation to contribute to a treatment protocol. We used porcine tissue to measure the temperature profile over time at 0, 2, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…On the other hand, ablative methods destroy the TZ by freezing the epithelium down to −80°C (cryotherapy) or by heating the epithelium to 100°C (thermal ablation), causing tissue necrosis. Tissue necrosis following cold or heat injury is expected to ensure the treatment of high‐grade lesions extending to the crypts, although some studies have questioned the adequacy of the depth of treatment achieved following thermal ablation 30,31 . An inability to identify the squamocolumnar junction correctly, and hence a failure to select appropriate cases for ablation, may be another reason for the variability in treatment outcomes after ablation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ablative methods destroy the TZ by freezing the epithelium down to −80°C (cryotherapy) or by heating the epithelium to 100°C (thermal ablation), causing tissue necrosis. Tissue necrosis following cold or heat injury is expected to ensure the treatment of high‐grade lesions extending to the crypts, although some studies have questioned the adequacy of the depth of treatment achieved following thermal ablation 30,31 . An inability to identify the squamocolumnar junction correctly, and hence a failure to select appropriate cases for ablation, may be another reason for the variability in treatment outcomes after ablation.…”
Section: Discussionmentioning
confidence: 99%
“…A temperature of –10°C or below is critical to induce cryonecrosis of tumors. 59 It is accomplished by direct and indirect cold-induced cell injury and death due to several mechanisms, such as intracellular ice crystal formation, thrombus formation causing ischemia, desiccation, and apoptosis. 60 Freeze-thaw cycles are prescribed in various duration, depending upon lung, kidney, liver, bone, or cervical tumors.…”
Section: Cryotherapymentioning
confidence: 99%
“…Challenges of cryotherapy comprise inconsistent and inadequate temperatures due to gas impurities, low pressure in gas tanks, and frequent use. 59 , 90 The fluctuation in temperature and gas impurity introduces ice blockage or clogging of the probe, which subsequently leads to reduced efficacy or failure of treatment. Some studies reported that superficial CO 2 cryotherapy achieved an average necrotic depth of 3.4 mm 24 hours after ablation, 90 , 91 while others reported depths of 6 mm 48 hours after ablation.…”
Section: Cryotherapymentioning
confidence: 99%
“…To eliminate numerical error, the boundary condition of the inner conductor and outer conductor in the coaxial cable is set as an ideal electric conductor, which satisfies → n × → E = 0. Boundaries of biological tissues and catheters are considered scattering boundary conditions to eliminate boundary reflections as defined in Equation (5).…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Thermal ablation surgery is an interventional treatment method for tumors [1], commonly including radiofrequency ablation (RFA) [2], and microwave ablation (MWA) [3] et al They make proteins of tumor cells irreversible through thermal effect, gradually losing cell function until death to achieve the purpose of the treatment [4]. It has become an important minimally invasive technique because of its advantages, such as being minimally invasive, leading to a fast recovery, and having a low cost [5,6]. At present, thermal ablation surgery is mainly based on the operational experience of clinicians [7].…”
Section: Introductionmentioning
confidence: 99%